High-affinity carboxyl-graphene oxide-based SPR aptasensor for the detection of hCG protein in clinical serum samples - Nan‐Fu Chiu; Chia-Tzu Kuo; Chen‐Yu Chen (2019)
The use of functionalized graphene oxide (fGO) has led to a new trend in the sensor field, owing to its high sensitivity with regards to sensing characteristics and easy synthesis procedures.In this study, we developed an ultra-sensitive carboxyl-graphene oxide (carboxyl-GO)-based surface plasmon resonance (SPR) aptasensor using peptides to detect human chorionic gonadotropin (hCG) in clinical serum samples. The carboxyl-GO based SPR aptasensor provided high affinity and stronger binding of peptides, which are great importance to allow for a non-immunological label-free mechanism. Also, it allows the detection of low concentrations of hCG, which are in turn considered to be important clinical parameters to diagnose ectopic pregnancies and paraneoplastic syndromes.The high selectivity of the carboxyl-GO-based SPR aptasensor for hCG recombinant protein was verified by the addition of the interfering proteins bovine serum albumin (BSA) and human serum albumin (HSA), which did not affect the sensitivity of the sensor. The carboxyl-GO-based chip can enhance the assay efficacy of interactions between peptides and had a high affinity binding for a ka of 17×106 M-1S-1. The limit of detection for hCG in clinical serum samples was 1.15 pg/mL.The results of this study demonstrated that the carboxyl-GO-based SPR aptasensor had excellent sensitivity, affinity and selectivity, and thus the potential to be used as disease-related biomarker assay to allow for an early diagnosis, and possibly a new area in the field of biochemical sensing technology.